2021
DOI: 10.3390/electronics10202542
|View full text |Cite
|
Sign up to set email alerts
|

SPSO Based Optimal Integration of DGs in Local Distribution Systems under Extreme Load Growth for Smart Cities

Abstract: Renewable energy-based distributed generators (DGs) are gaining more penetration in modern grids to meet the growing demand for electrical energy. The anticipated techno-economic benefits of these eco-friendly resources require their judicious and properly sized allocation in distribution networks (DNs). The preeminent objective of this research is to determine the sizing and optimal placing of DGs in the condensed DN of a smart city. The placing and sizing problem is modeled as an optimization problem to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Based on the outcomes, it can be concluded that odds and GWO have similar results. PSO outperformed the odds and GWO [ 29 , 30 ]. Table 3 illustrates the summary of the response times of each method.…”
Section: Simulation Results and Explanationmentioning
confidence: 99%
“…Based on the outcomes, it can be concluded that odds and GWO have similar results. PSO outperformed the odds and GWO [ 29 , 30 ]. Table 3 illustrates the summary of the response times of each method.…”
Section: Simulation Results and Explanationmentioning
confidence: 99%
“…PSO was successfully used for numerous parameter optimization problems in the last few decades, with recent achievements ranging from engineering applications, such as distributed generator integration of smart cities [36] to federated learning aggregation [37] and large-scale hyperparameter optimization of deep learning networks [38].…”
Section: Particle Swarm Optimization Of Derivative Ordermentioning
confidence: 99%
“…Ref. [26] presented a selective particle swarm optimization (SPSO) algorithm to solve an optimization model for optimal placement and sizing of distributed generators to reduce the distribution power losses, keeping technical constraints intact.…”
Section: Introductionmentioning
confidence: 99%